Super DWDM light source generation for personnel health data and security camera - Xaythavy Louangvilay; Somsak Mitatha; Preecha P. Yupapin (My University, 2010)
Abstract We propose a novel system of a dense wavelength division operation using the nonlinear micro ring resonators system that can be used to generate the broad output light spectra, whereas the significant increasing in channel capacity is obtained. A system consists of two micro and a nano ring resonators incorporating an add/drop filter that can be integrated into a single system. The large bandwidth signal is generated by using a soliton pulse propagating within a Kerr type nonlinear medium. The obtained results have shown the potential of using such system for broad band light source generation, amplification, storage and regeneration, whereas the amplified signals can be stored within a nano-waveguide, which is allowed to form the regeneration of the broad light spectra after amplification. The advantage is that the specific wavelength of the broadband source, for instance, 1.50 μm can provide the super dense wavelength division multiplexing channels, whereas the increasing in channel capacity of 200 times is achieved. The use of super dense wavelength division multiplexing for large population monitoring and closed circuit television for security using the personnel wavelength carrier and networking is described and discussed in details.
Keywords: Photonic and Optical Devices